Portfolio Assessment in Scope of Learning Competence-Based Islamic Religious Education (PAI) - Nurhayani; Maria Botifar; Deri Wanto (Journal of Educational Analytics, 2023)
Portfolio assessment is a method of continuous assessment with various collections of information or documentation of one's work taken during the learning process within a certain period of time and stored in a bundle in a systematic and organized manner. This assessment is considered by some educational researchers to be an alternative assessment in the modern world and much more reliable and valid than standard assessment. The portfolio assessment model is suitable for subjects that demand student learning outputs in terms of knowledge, skills and attitudes. The aspects measured in the portfolio assessment are the three domains of child psychology development, namely cognitive, affective and psychomotor. The components of the portfolio assessment include: (1) teacher notes, (2) student work results, and (3) student development profiles. Functions of portfolio assessment is as a tool for knowing the progress of competencies that have been achieved by students and diagnosing students' learning difficulties, providing feedback for the benefit of improving and perfecting the teaching and learning process.